A systematic study of Smart Water technology in improving the reservoir recovery performance - Khosravi, V. (Elsevier B.V., 2022)
Smart Water flooding, as an emerged technique in improving reservoir performance, demands systematic research. Determining the effective range of water ionic concentration has erupted the argumentative debates. Along with this, there is still a requirement to identify the in-situ wettability change and optimum water concentration. This research navigates to improve water chemistry knowledge using a systematic scheme of experimental and simulation approaches by the contribution of monovalent (Na+) and divalent (Ca2+) ions. To do this, one-factor-at-a-time (OFAT) and design of experiments (DOE) methods were employed to conduct contact angle and interfacial tension (IFT) measurements. Then, water force displacement tests and reservoir simulations were run to ascertain the in-situ changes and optimum brine concentration considering relative permeability, fractional flow, and ultimate oil recovery curves. In conclusion, two new analytical/empirical models were generated to predict contact angle and IFT based on brine concentration. The effective range of brine concentration was found to be 1000 to 15,000 ppm NaCl and 15,000 to 20,000 ppm CaCl2 in sandstone and 1000 to 10,000 ppm of both brines in carbonate. The IFT results showed the same range of concentration in sandstone, but irregular range in carbonate. In addition, according to water force displacement tests and simulation outcomes, the optimal value of Smart Water flooding was measured to be 8000 ppm NaCl-20,000 ppm CaCl2 brine concentration, resulting in about 4 increase in ultimate oil recovery. This study offers practical findings that advance water flooding technology understanding. Â© 2022 Elsevier B.V.